KARAKTER ARSITEKTUR RUMAH ULU DI TEPIAN SUNGAI KOMERING - Ina Indah Rahmadani; Wahyu Heny K. Sapardir; Ully Amrina (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2021)
Ulu house is a typical of platform house from the rural area of South Sumatra which still found in villages along the Komering River. Ulu houses in Kangkung Village are currently in poor condition. Some are modified, damaged and even collapsed. Ulu House is a witness of architectural development at that time. This is reflected in the appearance of the building and the spaces in it. Unfortunately, efforts to preserve traditional Ulu Houses in rural areas has not optimal yet. This research aimed to describe character of Ulu house in Kangkung Village. The results showed that the pattern of Ulu house was simple and very functional. The existing spaces describe the basic needs of space in house. This pattern also seems to be applied to today's housing development in general.